2012
DOI: 10.1111/j.1574-6941.2012.01433.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of bacterial symbionts in the Heteropteran,Blissus insularis

Abstract: Dense populations of extracellular bacteria were detected in midgut crypts of the southern chinch bug, Blissus insularis Barber (Hemiptera: Blissidae). Examination by epifluorescent and transmission electron microscopy revealed that the bacteria covered the luminal surface of the crypts and filled the entire lumen. Attempts to culture the extracellular endosymbionts in various media failed. Sequencing and phylogenetic analyses of 16S rRNA gene clones obtained from insects of five Florida populations showed hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
89
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(99 citation statements)
references
References 46 publications
(63 reference statements)
3
89
1
Order By: Relevance
“…For some insects, resistance has been attributed to the production of antimicrobial cuticular compounds (53)(54)(55). More recently there is growing evidence that some of these compounds are not produced by the insects themselves but by endogenous microbial flora, adding an interesting twist to coevolutionary scenarios (56,57). In other insects, specific behaviors, including heat seeking (behavioral fever), aggregation, and, in the case of social insects, grooming, have also been shown to be strategies for impeding or minimizing microbial infections (58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…For some insects, resistance has been attributed to the production of antimicrobial cuticular compounds (53)(54)(55). More recently there is growing evidence that some of these compounds are not produced by the insects themselves but by endogenous microbial flora, adding an interesting twist to coevolutionary scenarios (56,57). In other insects, specific behaviors, including heat seeking (behavioral fever), aggregation, and, in the case of social insects, grooming, have also been shown to be strategies for impeding or minimizing microbial infections (58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…This insect, a primary pest of St. Augustinegrass, Stenotaphrum secundatum (Walter) Kuntze (20,21), feeds on the grass phloem, resulting in diminished grass growth, yellowing and brown blade color, and the eventual death of grass patches (22,23). Investigations of multiple B. insularis field populations demonstrated that complex Burkholderia ribotypes were present within and among the populations (12). The copy number of the Burkholderia 16S rRNA gene increased with the age of B. insularis insects, and antibiotic treatment reduced Burkholderia numbers and slowed B. insularis development, pointing to a mutualistic Blissus-Burkholderia association (12).…”
mentioning
confidence: 99%
“…Investigations of multiple B. insularis field populations demonstrated that complex Burkholderia ribotypes were present within and among the populations (12). The copy number of the Burkholderia 16S rRNA gene increased with the age of B. insularis insects, and antibiotic treatment reduced Burkholderia numbers and slowed B. insularis development, pointing to a mutualistic Blissus-Burkholderia association (12). Another chinch bug species, Cavelerius saccharivorus Okajima (Heteroptera: Lygaeoidea: Blissidae), also harbors Burkholderia spp.…”
mentioning
confidence: 99%
See 2 more Smart Citations